(untitled) (Innovative professional education, 2024)
Ukraine has experienced many challenges in digitalizing education due to the COVID-19 pandemic and military operations. This issue was especially aggravated due to the unpreparedness of the infrastructure, limited access to the Internet, the lack of quality electronic educational resources, and insufficient training of teachers. However, the educational process has adapted to different formats: online, offline, and mixed. Despite the existing problems, Ukraine has taken a significant step in the direction of the digital transformation of education, considering the complexity of the military context. The article reveals the main directions of digitalization of professional education in the conditions of a full-scale invasion of the Russian Federation on the territory of sovereign Ukraine.